Preservation Not Paralysis: Reflections on Launching a Born-Digital Preservation Program. Issue 4 (December 2021) - Herzinger, Kyna; Daniels, Caroline; Fox, Heather
Born-digital materials are fleeting and fragile, yet digital preservation has been a challenge with its evolving methods and technical requirements. Added to this, many libraries, archives, and museums lack broad capacity to preserve born-digital materials with confidence. This case study offers an example of how one minimally resourced public university navigated the landscape to establish a born-digital preservation program. It distills the immense literature into practical, manageable actions while utilizing limited resources to meet feasible goals. In recognizing the hurdles that can keep an institution from taking steps to establish a digital preservation program, this case study seeks to empower librarians, archivists, and museum professionals as it traces a process that can serve as a foundation for maintaining and incrementally growing a robust digital preservation program.